IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ARABIC LEARNING: LEARNING STRATEGIES - Khotami, Ahmad Rosyid; Pandi, Supandi; Hidayatullah, Syarif (Kitaba, 2024)
Curriculum in Arabic language learning at MTS Al-Ishlahuddiny. This qualitative descriptive study collected data through documentation, observation, and interviews from primary and secondary sources. Data analysis involved reduction, presentation, and drawing conclusions. The findings reveal that Arabic language learning at MTS Al-Ishlahuddiny integrates the Ministry of Education and Culture's curriculum with KMI Kediri, Salafiyah, and Tahfidz Al-Qur'an curricula, which enhances Arabic learning outcomes. The implementation includes various programs: National Seminar on Arabic for Teachers, the formation of a language section within student organizations, and effective Arabic learning both in and outside the classroom. In-class learning employs group-based lughawiyah and independent curriculum-based methods. Extracurricular activities include muhāḍarah (speeches), muhādaṡah (conversations), musyāhadah al-aflām al-arābiyah (watching Arabic films), mahkāmah al-lughah (language court), Arabic drama contests, and both internal and external competitions.